Managing Academic Integrity in Canadian Engineering Schools - deMontigny, David (Canadian Perspectives on Academic Integrity, 2021)
Within the literature a lot of research has been published on academic misconduct, including why students cheat, how they cheat, and what can be done to curb the behavior. Very little research had been done to determine how schools have addressed academic integrity from a management or administrative perspective. This presentation highlights the work from a book chapter I submitted to a national project on academic integrity in Canadian post-secondary institutions. This work focused on how engineering schools and the professional engineering regulators were promoting academic integrity and dealing with academic misconduct. A survey was provided to all 43 Canadian engineering schools and the 12 provincial and territorial engineering regulators. The survey covered topics related to integrity, misconduct, professionalism, and administrative strategies and procedures. These results have been put into context with existing literature and potential best practices. This presentation will be of interest to students, instructors and administrators from all faculties. Students will learn about academic integrity and misconduct from an administrator’s perspective. Instructors will lean how to improve academic integrity in their courses. Administrators will be exposed to broader policy and practice content.